Analyzing the effect of trust and perceived value on purchase intention (case study of Shopee) - Rafsandjani, Rieza Firdian (MEC-J (Management and Economics Journal), 2018)
The progress of marketing is accelerating, nowadays people do not have to waste their time walking to the store to buy things. They just need to browse the internet and search for what they want and get it in no time. With this convenience and speed, online shopping interest is increasing. When customers intend to purchase products from the internet, they consider values and perceived beliefs. The main purpose of this study is to analyze the influence of the perception of values and beliefs on purchasing intentions in Shopee. Data were collected from 50 respondents and multiple regression analysis was used to test the relationship between variables. Based on the indicators described on the perception of value that is the value of experimental, functional value, market value and on the belief that is the ability, virtue, integrity then they have a significant partial influence on the purchase intention. The results can be maintained by giving customers the best value and earning their trust to maintain their purchase intentions.Â